In-plane porous Co3O4 nanosheet assembled 3D hierarchical clusters grown on stainless steel mesh as binder-free anodes for high performance lithium ion batteries. Issue 18 (23rd April 2018) - Xie, Qinxing; Song, Rui; Zhao, Peng; Zhang, Yufeng; Wu, Shihua; Xie, Dongliang
Abstract : In-plane porous Co3 O4 nanosheet assembled hierarchical clusters anchored on SSM were fabricated as high performance anodes for LIBs. The nanosheets are composed of primary nanoparticles and secondary nanorods. Abstract : In-plane porous Co3 O4 nanosheet assembled three-dimensional (3D) hierarchical clusters anchored on stainless steel mesh (Co3 O4 @SSM) were successfully fabricated using a hydrothermal method, followed by a low-temperature calcination process. The individual Co3 O4 nanosheets are composed of numerous primary nanoparticles and secondary nanorods, and their thickness is correlated with the Co 2+ concentration of the aqueous solution used for hydrothermal synthesis. The as-prepared materials were investigated as binder-free anodes for lithium ion batteries, and the results demonstrate a maximal specific capacity of up to 2030 mA h g −1 at a current density of 100 mA g −1, as well as superior cycling stability and rate capability due to the in-plane porous feature, optimized thickness and hierarchical assembly with abundant interstitial space of the nanosheets.